Drp1/Fis1-Dependent Pathologic Fission and Associated Damaged Extracellular Mitochondria Contribute to Macrophage Dysfunction in Endotoxin Tolerance. Issue 6 (24th January 2022) - Mukherjee, Riddhita; Tompkins, Carly A.; Ostberg, Nicolai P.; Joshi, Amit U.; Massis, Liliana M.; Vijayan, Vijith; Gera, Kanika; Monack, Denise; Cornell, Timothy T.; Hall, Mark W.; Mochly-Rosen, Daria; Haileselassie, Bereketeab
Abstract : OBJECTIVES: Recent publications have shown that mitochondrial dynamics can govern the quality and quantity of extracellular mitochondria subsequently impacting immune phenotypes. This study aims to determine if pathologic mitochondrial fission mediated by Drp1/Fis1 interaction impacts extracellular mitochondrial content and macrophage function in sepsis-induced immunoparalysis. DESIGN: Laboratory investigation. SETTING: University laboratory. SUBJECTS: C57BL/6 and BALB/C mice. INTERVENTIONS: Using in vitro and murine models of endotoxin tolerance (ET), we evaluated changes in Drp1/Fis1-dependent pathologic fission and simultaneously measured the quantity and quality of extracellular mitochondria. Next, by priming mouse macrophages with isolated healthy mitochondria (MC ) and damaged mitochondria, we determined if damaged extracellular mitochondria are capable of inducing tolerance to subsequent endotoxin challenge. Finally, we determined if inhibition of Drp1/Fis1-mediated pathologic fission abrogates release of damaged extracellular mitochondria and improves macrophage response to subsequent endotoxin challenge. MEASUREMENTS AND MAIN RESULTS: When compared with naïve macrophages (NMs), endotoxin-tolerant macrophages (ETM) demonstrated Drp1/Fis1-dependent mitochondrial dysfunction and higher levels of damaged extracellular mitochondria (Mitotracker-Green + events/50 μL: ETM = 2.42 × 10 6 ± 4, 391 vs NM = 5.69 × 10 5 ± 2, 478; p < 0.001). Exposure of NMs to damaged extracellular mitochondria (MH ) induced cross-tolerance to subsequent endotoxin challenge, whereas MC had minimal effect (tumor necrosis factor [TNF]-α [pg/mL]: NM = 668 ± 3, NM + MH = 221 ± 15, and NM + Mc = 881 ± 15; p < 0.0001). Inhibiting Drp1/Fis1-dependent mitochondrial fission using heptapeptide (P110), a selective inhibitor of Drp1/Fis1 interaction, improved extracellular mitochondrial function (extracellular mitochondrial membrane potential, JC-1 [R/G] ETM = 7 ± 0.5 vs ETM + P110 = 19 ± 2.0; p < 0.001) and subsequently improved immune response in ETMs (TNF-α [pg/mL]; ETM = 149 ± 1 vs ETM + P110 = 1, 150 ± 4; p < 0.0001). Similarly, P110-treated endotoxin tolerant mice had lower amounts of damaged extracellular mitochondria in plasma (represented by higher extracellular mitochondrial membrane potential, TMRM/MT-G: endotoxin tolerant [ET] = 0.04 ± 0.02 vs ET + P110 = 0.21 ± 0.02; p = 0.03) and improved immune response to subsequent endotoxin treatment as well as cecal ligation and puncture. CONCLUSIONS: Inhibition of Drp1/Fis1-dependent mitochondrial fragmentation improved macrophage function and immune response in both in vitro and in vivo models of ET. This benefit is mediated, at least in part, by decreasing the release of damaged extracellular mitochondria, which contributes to endotoxin cross-tolerance. Altogether, these data suggest that alterations in mitochondrial dynamics may play an important role in sepsis-induced immunoparalysis.